Perancangan Visual Media Promosi Romokalisari Adventure Land Bagi Segmen Keluarga - Pramesti, Irna Yuli; Yani, Aditya Rahman; Aji, Restu Ismoyo (Universitas Pahlawan Tuanku Tambusai, 2024)
The focus of this study is the design of media promotion of a family tourist destination in Surabaya, Romokalisari Adventure Land. By applying the Design Thinking method that involves six stages, namely definition, Research, Interpretation, ideation, prototyping, and evaluation, the main goal is to increase brand awareness through visual communication design that has artistic, communicative, and persuasive value. In collecting data, this study used a variety of methods such as interviews, observations, and questionnaires, as well as analyzing the results with a qualitative descriptive approach and SWOT analysis. The findings of this study confirm that the effective application of promotional media can result in optimization in brand awareness, through the utilization of various media, such as social media, billboards, and other printed materials, both as Main and supporting media.